Immigration, inversion et industrie à Puebla. La trajectoire patronale des frères Díaz Rubín 1878-1914 (Tzintzun, Revista de Estudios Históricos, 2016)
In this paper we analyze the Company History of Diaz Rubin brothers in Pueblabetween 1878 and 1914. Diaz Rubin family came from Asturias in order to settledown in Puebla in the last quarter of the twentieth century. First of all, we haveto mention that their immigrant condition was a defining factor to start theircommercial and industrial business because they continued a family traditionwhich was a very common pattem among the Spanish groups during Porfirio Diazperiod. The article also analyzes the water and land hoarding made by Dfaz Rubinbrothers in order to eam money to invest in their businesses. This paper highlightsthree main factors in the business activity: the buyout and modernization of thesugar mills in Izicar, the setting up of textile factories in Puebla and Atlixcoand the establishment of grocery stores. Furthermore, this article studies otherinvestments made on banking and railways.
Keywords: Díaz Rúbin; Spanish immigration; Porfiriato; entrepreneurs